2006
DOI: 10.1534/genetics.106.059238
|View full text |Cite
|
Sign up to set email alerts
|

Using Substrate-Binding Variants of the cAMP-Dependent Protein Kinase to Identify Novel Targets and a Kinase Domain Important for Substrate Interactions in Saccharomyces cerevisiae

Abstract: Protein kinases mediate much of the signal transduction in eukaryotic cells and defects in kinase function are associated with a variety of human diseases. To understand and correct these defects, we will need to identify the physiologically relevant substrates of these enzymes. The work presented here describes a novel approach to this identification process for the cAMP-dependent protein kinase (PKA) in Saccharomyces cerevisiae. This approach takes advantage of two catalytically inactive PKA variants, Tpk1 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 48 publications
4
85
1
Order By: Relevance
“…Second, we recently analyzed several Ribi genes by chromatin immunoprecipitation and showed that Dot6 is bound to their promoters in vivo during growth under conditions of nutrient limitation but not during growth in rich medium (19). Moreover, Deminoff et al (23) have shown that PKA phosphorylates Dot6 in vitro, and we have recently found that Dot6 and Tod6 exhibit increased phosphorylation on several PKA sites after addition of glucose to glycerol-grown cells (Table S2). Loewith and colleagues (24) have determined that phosphorylation of Dot6 and Tod6 is altered by rapamycin in a Sch9-dependent manner.…”
Section: Discussionmentioning
confidence: 81%
“…Second, we recently analyzed several Ribi genes by chromatin immunoprecipitation and showed that Dot6 is bound to their promoters in vivo during growth under conditions of nutrient limitation but not during growth in rich medium (19). Moreover, Deminoff et al (23) have shown that PKA phosphorylates Dot6 in vitro, and we have recently found that Dot6 and Tod6 exhibit increased phosphorylation on several PKA sites after addition of glucose to glycerol-grown cells (Table S2). Loewith and colleagues (24) have determined that phosphorylation of Dot6 and Tod6 is altered by rapamycin in a Sch9-dependent manner.…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with this notion, mutation of the APE glutamate to lysine in ILK may reduces substrate affinity (50), or alternatively, may reduce affinity for the associated kinase responsible for substrate phosphorylation (51). Likewise, mutation of the arginine of subdomain XII in yeast PKA was shown to affect binding and release of protein substrates (52). It is interesting that, although they are not exposed to solvent, these residues are indirectly contributing to substrate binding.…”
Section: Discussionmentioning
confidence: 93%
“…Instead, the binding was specific to two Tpk1 variants, Tpk1 KH and Tpk1 R324A , that had alterations within a specific C-terminal region of the Tpk1 kinase domain. 65 This observation could help explain why previous attempts to generate "substrate-trapping" versions of other protein kinases had failed. Alteration of the analogous residues targeted in these previous studies were found to have no significant effect on Tpk1-substrate interactions.…”
Section: Kinase Substrate Trap Assaymentioning
confidence: 99%
“…25 Our laboratory recently identified catalytically-defective versions of the S. cerevisiae PKA isoform, Tpk1, that exhibited a stable interaction with a number of known substrates. 65 This binding was specific to substrates and was easily detected with methods, like two-hybrid and coimmunoprecipitation assays, that can be readily scaled up for high throughput analyses. The general potential of this approach was illustrated by the identification of a novel PKA substrate, the Dot6 protein from S. cerevisiae.…”
Section: Kinase Substrate Trap Assaymentioning
confidence: 99%
See 1 more Smart Citation